The Relationship between Fitness and Healthy Lifestyle (Balneo and PRM Research Journal, 2022)
Background: In our study we will refer to the benefits of practicing appropriate fitness exercises that can contribute to maintaining or returning to a closer weight, to achieving an adequate physical condition reflected in self-confidence and to adopting a healthy lifestyle.; (2) Methods:.Our theoretical study is based on the analysis of perspectives offered by specialists in fields complementary to physical education, in order to understand not only from a medical but also a social perspective, the importance of fitness in the lives of young people. (3) Results: We believe that the physical exercises that make up the fitness set have beneficial effects on the human body, from the point of view: morphogenetic, physiological, educational, prophylactic and curative. (4) Conclusions: In this context, we believe that it is necessary to reconsider the benefits of fitness - a good remedy against sedentarism and aging, being able to delay, diminish or completely prevent the mechanisms associated with these processes (arterial diseases, diabetes, high cholesterol, etc.). Fitness is part of a healthy lifestyle